2021
DOI: 10.1002/ijc.33785
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of CDK 4/6 inhibitors and its impact on treatment choices in HR+/HER2− advanced breast cancer patients: A study of the Dutch SONABRE Registry

Abstract: In August 2017, cyclin‐dependent kinase 4/6 (CDK4/6) inhibitors combined with endocrine therapy have been reimbursed in the Netherlands for patients with hormone receptor positive (HR+), HER2 negative (HER2−) advanced breast cancer (ABC). This study evaluates the implementation of CDK4/6 inhibitors and changes in treatment choices in the Netherlands. All patients diagnosed with HR+/HER2− ABC in 2009 to 2018 in seven hospitals were selected from the Southeast Netherlands Advanced Breast cancer (SONABRE) registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The study by Meegdes et al in 2021 reported on CDK4/6i treatment usage in Dutch patients with HR+/HER2− aBC based on data from the Southeast Netherlands Advanced Breast cancer (SONABRE) Registry from 2009 to 2018. This study found that since August 2017 when CDK4/6i were reimbursed in the Netherlands, CDK4/6i combined with ET was received by 31% of 214 patients in 1L, and by 44% of 71 patients in 2L with no prior exposure to CDK4/6i [ 31 ]. Additionally, CDK4/6i combined with ET usage gradually increased over time from 2014 onward in all lines reported (i.e., 1L–3L), while the use of chemotherapy, ET, and mTORi decreased [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Meegdes et al in 2021 reported on CDK4/6i treatment usage in Dutch patients with HR+/HER2− aBC based on data from the Southeast Netherlands Advanced Breast cancer (SONABRE) Registry from 2009 to 2018. This study found that since August 2017 when CDK4/6i were reimbursed in the Netherlands, CDK4/6i combined with ET was received by 31% of 214 patients in 1L, and by 44% of 71 patients in 2L with no prior exposure to CDK4/6i [ 31 ]. Additionally, CDK4/6i combined with ET usage gradually increased over time from 2014 onward in all lines reported (i.e., 1L–3L), while the use of chemotherapy, ET, and mTORi decreased [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study found that since August 2017 when CDK4/6i were reimbursed in the Netherlands, CDK4/6i combined with ET was received by 31% of 214 patients in 1L, and by 44% of 71 patients in 2L with no prior exposure to CDK4/6i [ 31 ]. Additionally, CDK4/6i combined with ET usage gradually increased over time from 2014 onward in all lines reported (i.e., 1L–3L), while the use of chemotherapy, ET, and mTORi decreased [ 31 ]. An observational study by Cui et al in 2021 investigated CDK4/6i treatment usage in nearly 4000 women diagnosed with HR+/HER2− mBC in the USA between 1 January, 2013 and 31 January, 2019 based on data from the Flatiron Health database.…”
Section: Resultsmentioning
confidence: 99%
“… 7 , 8 , 9 In a prior study of the SONABRE Registry we observed that the implementation of CDK4/6 inhibitors was somewhat lower than in other Western countries, mostly explained by the Dutch guideline recommendation that the use of CDK4/6 inhibitors in second line may be considered while awaiting the results of the SONIA study. 10 , 23 It is of importance to notice that most patients in the SONABRE Registry were treated with palbociclib as CDK4/6 inhibitor. Although no conclusions on the effectiveness of CDK4/6 inhibitors can be made from our study, our results seem to support the hypothesis that all types of CDK4/6 inhibitors may provide an overall survival benefit, despite the ongoing discussion regarding the variable significance in the phase 3 trials.…”
Section: Discussionmentioning
confidence: 99%
“…In line with guidelines, the results of the SONABRE Registry indicates that the use of everolimus is postponed to later lines of treatment since the implementation of CDK4/6 inhibitors. 10 By the introduction of PI3 kinase inhibitors in more recent years, we expect that well-chosen and more effective second- and further lines of endocrine and targeted therapies may contribute to further improvements in overall survival of patients with HR+/HER2− ABC. 24 , 25 The improved overall survival we observed in this real-world setting despite a reduced use of chemotherapy, indicates the value of endocrine and targeted therapy and fits the earlier findings of relative chemotherapy resistance in this particular breast cancer subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation